2022
DOI: 10.1111/jog.15356
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of human epididymis protein 4 expression in patients with endometrial cancer: A systematic review and meta‐analysis

Abstract: Background: There is no consensus on the correlation between human epididymis protein 4 (HE4) and prognosis of endometrial cancer (EC). Therefore, we performed a meta-analysis to assess the relationship between HE4 and prognosis of EC. Methods: In this systematic review and meta-analysis, the databases were searched. Correlation of serum or tissue HE4 with clinicopathological characteristics was determined by odds ratio (OR) or standardized mean difference (SMD) with 95% confidence interval (CI), respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Similar findings were presented by Han Li-Na et al [23], who conducted a meta-analysis assessing the link between HE4 and prognosis in EC. Their conclusion was that the HE4 marker may be a better predictor of EC than CA125, and high serum levels of HE4 were associated with poor OS and disease-free survival [23].…”
Section: Ca125 and Its Combinations With Other Parameters; Algorithms...supporting
confidence: 86%
See 1 more Smart Citation
“…Similar findings were presented by Han Li-Na et al [23], who conducted a meta-analysis assessing the link between HE4 and prognosis in EC. Their conclusion was that the HE4 marker may be a better predictor of EC than CA125, and high serum levels of HE4 were associated with poor OS and disease-free survival [23].…”
Section: Ca125 and Its Combinations With Other Parameters; Algorithms...supporting
confidence: 86%
“…A metaanalysis carried out by Li J et al [22] indicated that when histologic type and stage are not considered, the serum HE4 assay is a superior diagnostic tool for EC because of its increased sensitivity compared to the CA125 assay [22]. Similar findings were presented by Han Li-Na et al [23], who conducted a meta-analysis assessing the link between HE4 and prognosis in EC. Their conclusion was that the HE4 marker may be a better predictor of EC than CA125, and high serum levels of HE4 were associated with poor OS and disease-free survival [23].…”
Section: Ca125 and Its Combinations With Other Parameters; Algorithms...mentioning
confidence: 64%
“…HE4 was shown to have a higher sensitivity in patients with early-stage disease [30]. Han L. N. et al [31] conducted a meta-analysis of 38 published studies evaluating the association between HE4 and prognosis in endometrial cancer (EC). They found that high serum HE4 levels were associated with FIGO stages III-IV as well as with poor overall survival and disease-free survival.…”
Section: He4mentioning
confidence: 99%
“…They found that high serum HE4 levels were associated with FIGO stages III-IV as well as with poor overall survival and disease-free survival. Therefore, when compared with CA125, the serum HE4 marker may be a better prognostic indicator for EC [31].…”
Section: He4mentioning
confidence: 99%
“…24 Recent studies also revealed that serum HE4 was a useful diagnostic marker for other types of cancer, such as lung cancer 25,26 and endometrial cancer. 27,28 In addition, serum HE4 increases in HF patients, and higher HE4 predicts worse outcomes in HF patients. 29 Notably, previous studies showed that both serum tumor markers and their pleural fluid counterparts helped diagnose MPE, 13 and the diagnostic accuracy of pleural fluid tumor markers was higher than their serum counterparts.…”
Section: Introductionmentioning
confidence: 99%